Children's picturebooks : the art of visual storytelling - Salisbury, Martin; Styles, Morag; 4 ov; Smy, Pam.; Riveros, Ida.; Laurence King Publishing; Studio Ten and a Half. (London : Laurence King Pub., 2012)
Children's picturebooks are the very first books we encounter, and they form an important, constantly evolving, and dynamic sector of the publishing world. But what does it take to create a successful picturebook for children? In seven chapters, this book covers the key stages of conceiving a narrative, creating a visual language and developing storyboards and design of a picturebook. The book includes interviews with leading children's picturebook illustrators, as well as case studies of their work. The picturebooks and artists featured hail from Australia, Belgium, Cuba, France, Germany, Hungary, Ireland, Italy, Japan, Norway, Poland, Portugal, Russia, Singapore, South Korea, Spain, Taiwan, the UK and the USA. In this publication, Martin Salisbury and Morag Styles introduce us to the world of children's picturebooks, providing a solid background to the industry while exploring the key concepts and practices that have gone into the creation of successful picturebooks.
A brief history of the picturebook -- The picturebook maker's art -- The picturebook and the child -- Word and image, word as image -- Suitable for children? -- Print and process : the shock of the old -- The children's publishing industry.
"Design: Studio Ten and a Half ; Cover art: Beatrice Alemagna ; Research assistant: Pam Smy ; Book photography: Ida Riveros"--t.p. verso.
Includes bibliographical references (p. 187-188) and index.
Keywords: Illustrated children's books; Children's literature -- Illustrations; Illustration of books; Picture books for children